1991
DOI: 10.1002/1097-0142(19910501)67:9<2390::aid-cncr2820670928>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of simultaneous determinations of glucosaminylation and fucosylation indices of alpha-fetoprotein in the differential diagnosis of neoplastic diseases of the liver

Abstract: The degrees of glucosaminylation (glucosaminylation index) and fucosylation (fucosylation index) of alpha-fetoprotein (AFP) were determined in serum samples of 351 patients with hepatocellular carcinoma (HCC), 47 with carcinoma metastatic to the liver from digestive organs, five with mixed cholangiocellular and HCC, and 176 with benign liver diseases. The glucosaminylation index of AFP in patients with carcinoma metastatic to the liver (42 +/- 23%, mean +/- SD) was significantly higher than that in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…The identification of AFP with O-linked glycans is a surprising finding as several previous investigators should have detected these isoforms (Yoshima et al, 1980;Yamashita et al, 1983Yamashita et al, , 1993Aoyagi et al, 1991). Under different experimental conditions, O-linked and N-linked glycans can be differentially released from proteins by hydrazinolysis (Patel et al, 1993).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The identification of AFP with O-linked glycans is a surprising finding as several previous investigators should have detected these isoforms (Yoshima et al, 1980;Yamashita et al, 1983Yamashita et al, , 1993Aoyagi et al, 1991). Under different experimental conditions, O-linked and N-linked glycans can be differentially released from proteins by hydrazinolysis (Patel et al, 1993).…”
Section: Discussionmentioning
confidence: 93%
“…Previous reports have suggested that AFP glycoforms in HCC and NSGCT carry tri-antennary or N-acetylglucosaminylated bi-antennary carbohydrate structures making them non-reactive to ConA (Yamashita et al, 1983;Aoyagi et al, 1991). Yamashita et al (1983) identified acetylglucosaminylated bi-antennary N-glycans in AFP purified from human yolk sac tumours grown in nude mice in support of this proposal.…”
Section: Discussionmentioning
confidence: 99%
“…24-27 ␣1-6 Fucosylation of serum AFP from patients with HCC is one of the most representative of these aberrant elevations of fucosylation involved in malignant conditions and recently has been clinically proposed as a specific tumor marker for HCC. 5,6,28 Similarly, in patients with HCC, N-glycans contained in some serum glycoproteins such as ␣ 1 -antitrypsin 29 and transferrin 30 also increase fucosylation. Because the elevation in ␣1-6 fucosylation of most N-glycans attached on serum glycoproteins occurs in patients with hepatoma, it has been suggested that these alterations might be the manifestations of increased ␣1-6 FucT activity in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…To date, it has been reported by a number of investigators that the fucosylation of serum AFP is significantly elevated at a high frequency in patients with HCC compared with that of patients with chronic liver diseases without HCC, [5][6][7]28 and these have been considered as manifestation of an increased ␣1-6 FucT activity in HCC tissues. However, to our surprise, in human liver samples, the level of ␣1-6 FucT was frequently elevated in adjacent nontumor liver tissues over a wide range and showed a trend toward increasing with the progression of chronic liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical heterogeneity of these patients prevents straightforward identifi-cation of causative genes. An additional complicating factor is the occurrence of secondary causes of type II TIEF profiles, including hemolytic uremic syndrome (HUS) with the presence of pneumococcal sialidase in plasma (6 ), or severe liver pathology (7)(8)(9). Given that some of the CDG type II defects present with severe hepatopathy as well, these factors may delay diagnosis.…”
Section: © 2010 American Association For Clinical Chemistrymentioning
confidence: 99%